Evaluation of the Purity of Plant Genetic Material of Dry Seeds and Modern Leaves of Some Local Barley (Hordeum vulgare L.) Varieties using CTAB, SDS and Mixture Extraction Solutions (CTAB and SDS) (مجلة العلوم الشاملة, 2026)
The extract of genomic DNA from dry seeds as well as young leaves of various local Hordeum vulgare, or barley plants, the research evaluates the efficiency of three plant DNA isolation methods such as CTAB, SDS, and the integration of both. The CTAB extraction procedure effectively eliminated impurities that are linked to inhibitory chemicals, as evidenced by spectrophotometric studies. This procedure also yielded the highest DNA purity for both fresh leaves and dry seeds. At electrophoresis exposed at 70 V for 60 minutes, for DNA migration patterns, which showed intact and recoverable genomic DNA, the results validated the successful extraction of plant genetic material. The spectrophotometric experiments indicated that the CTAB protocol of extraction was successful in the removal of contaminants associated with inhibiting compounds. Furthermore, this approach resulted in the maximum DNA purity for fresh leaves and dried seeds. The research outcome in the earlier stage corroborated CTAB efficiently, which separated DNA from secondary metabolite-rich plants. Furthermore, lower purity values (about 1.30) have been obtained utilizing the combined method (CTAB + SDS), indicating the presence of residual impurities. Because of limited effectiveness in tissues containing polysaccharides as well as phenolic compounds, SDS alone yielded very low-quality DNA (purity ~1.65).